Orchid Reintroduction Based on Seed Germination-Promoting Mycorrhizal Fungi Derived From Protocorms or Seedlings - Zhao, Da-Ke; Selosse, Marc-André; Wu, Limin; Luo, Yan; Shao, Shi-Cheng; Ruan, Yong-Ling (Frontiers in Plant Science, 2021)
Orchids are among the most endangered in the plant kingdom. Lack of endosperm in their seeds renders orchids to depends on nutrients provided by orchid mycorrhizal fungi (OMF) for seed germination and seedling formation in the wild. OMF that parasitize in germination seeds is an essential element for orchid seedling formation, which can also help orchid reintroduction. Considering the limitations of the previous orchid reintroduction technology based on seed germination-promoting OMF (sgOMF) sourced from orchid roots, an innovative approach is proposed here in which orchid seeds are directly co-sown with sgOMF carrying ecological specificity from protocorms/seedlings. Based on this principle, an integrative and practical procedure concerning related ecological factors is further raised for re-constructing long-term and self-sustained orchid populations. We believe that this new approach will benefit the reintroduction of endangered orchids in nature.